Storage study of cereal bars formulated with banana peel flour Bioactive compounds and texture properties - Carvalho, Vania Silva; Conti-Silva, Ana Carolina [UNESP] (Emerald Group Publishing Ltd, 2018)
Purpose - This paper aims to examine the bioactive compounds and texture properties of cereal bars formulated with banana peel flour during storage. Design/methodology/approach - Seven cereal bars were produced and stored during 11 months, under vacuum and protected from the light. The total phenolic compounds, the activity antioxidant by ABTS [ 2,2''-Azino-bis( 3-ethylbenzothiazoline-6-sulfonic acid)] method, the DPPH (2,2-diphenyl-1-picryl-hydrazyl-hydrate) method expressed as EC50 (concentration required to reduce the original amount of free radicals by 50 per cent) and texture properties were evaluated over the storage period. Findings - In general, total phenolic compounds decreased during storage (from 4.19 to 1.11 mg GAE.g-1f.w.). Although the total antioxidant activity (ABTS method) increased during the fifth month, it reduced during storage (from 3.41 to 0.30 mu mol TE.g-1f.w.); and the EC50 was not modified in many formulations, though it decreased in other formulations during storage period (from 3913 to 19221 g fruit.g-1 DPPH). The force of rupture began to increase in the fourth month (reaching 62.4 N), and hardness began to increase in the ninth month (reaching 444 N). The formulation and time factors influenced the total phenolic compounds, total antioxidant activity (ABTS method), force of rupture and hardness, while EC50 was only influenced by the formulation (p-value = 0.001). A principal component analysis showed that time had little effect on the most important characteristics considered in description of the cereal bars. Originality/value - Cereal bars can be consumed up to the third month of storage, considering the texture of the products. Moreover, the presence of bioactive compounds in cereal bars depends on the addition of banana peel flour, which it contributes to the insertion of total phenolic compounds and total antioxidant activity in cereal bars, aggregating functional properties in these products.
Keywords: DPPH; Texture profile analysis; ABTS; Force of rupture; Total phenolics compounds